POPULARITY OF CHOOSING FOB AND CIF FOR INTERNATIONAL CONTAINER TRADE - Kulpreeyawat, Tarin (Journal of MCU Nakhondhat, 2023)
The objectives of this research article were to study the reason of choosing FOB and CIF for international container trade. This qualitative research is composed of gathered data from the academic articles, statutory provisions and textbooks. The findings revealed that the International Chamber of Commerce (ICC) encourages the use of ‘any mode of transport’ terms (FCA, CPT, CIP, DAP, DPU and DDP) instead of the ‘maritime’ Incoterms (FAS, FOB, CFR and CIF). According to the ICC, maritime terms are not appropriate, and thus should not be used in container trade. But in practice, the parties still choose FOB or CIF for an international container trade. There are two reasons for choosing FOB and CIF for international container trade. First of all, the issuing bank has set the documents that the seller must tender a ‘on board’ bill of lading for L/C payment, in order to ensure that the goods have been loaded on board the vessel. The issuing bank therefore requires a container trade to be contracted at the price under FOB or CIF. Secondly, if the deal is agreed with FCA, the risk in the goods is transferred from the seller to the buyer at the time the goods are delivered to the carrier. So before the containers are lifted on board the ship, the buyer has to pay the Terminal Handling Charges (THC). When the buyer does not want to pay the Terminal Handling Charges (THC), the buyer still chooses the FOB.